The Pengelolaan Media Sosial: Strategi Peningkatan Kualitas Belajar Yang Efektif Bagi Siswa Smk Prima Unggul, Kota Tangerang - Rahman, Abdul Rahman HI; Utamie Subiakto, Vania; Tri Atmodjo, Juwono (LOSARI DIGITAL, 2024)
The aim of this community service activity is to improve social media management in an effort to improve the quality of effective learning for Prima Unggul Vocational School students, Tangerang City. This activity provides an opportunity to develop understanding through the use of social media such as Facebook, Instagram, YouTube, and TikTok allowing students to create interesting content, share information quickly, and facilitate effective collaboration. The activity stages carried out are divided into 2 sessions, where the first session is the material explanation stage session and the second session is the simulation session. Initially, students were given a pretest before entering the material explanation stage, after that, the author also gave games to students by asking basic questions to train the students' thinking skills and analytical skills. Enter the material explanation session. The third stage, Practice or Simulation Stage. As a result of this PPM activity, it is known that there is high enthusiasm from the participants, from the overall activity it is known that 90% of them have increased knowledge and motivation to be able to improve the quality of learning from managing social media. The assistance of the service team provides models and methods for managing social media properly and correctly to determine the quality of student learning.